Phase-Transition-Induced Pattern Formation Applied to Basic Research on Homeopathy: A Systematic Review - Kokornaczyk, Maria Olga; Scherr, Claudia; Bodrova, Natalia Borisovna; Baumgartner, Stephan (Homeopathy, 2018)
Background Methods based on phase-transition-induced pattern formation (PTPF) are increasingly used in medical research. Frequent application fields are medical diagnosis and basic research in homeopathy. Here, we present a systematic review of experimental studies concerning PTPF-based methods applied to homeopathy research. We also aimed at categorizing the PTPF methods included in this review.Materials and Methods Experimental studies were collected from scientific databases (PubMed, Web of Science, Russian eLibrary) and from experts in the research field in question, following the PRISMA guidelines. The studies were rated according to pre-defined scientific criteria.Results The review included 15 experimental studies. We identified seven different PTPF methods applied in 12 experimental models. Among these methods, phase-transition was triggered through evaporation, freezing, or solution, and in most cases led to the formation of crystals. First experimental studies concerning the application of PTPF methods in homeopathic research were performed in the first half of the 20th century; however, they were not continued in the following years. Only in the last decade, different research groups re-launched the idea, introducing new experimental approaches and computerized pattern evaluation techniques. The here-identified PTPF methods are for the first time proposed to be classified as one group of methods based on the same basic physical phenomenon.Conclusions Although the number of experimental studies in the area is still rather limited, the long tradition in the application of PTPF methods and the dynamics of the present developments point out the high potential of these methods and indicate that they might meet the demand for scientific methods to study potentized preparations.
Keywords: phase-transition; crystallization; patterns; homeopathy; potencies